PERMINTAAN BERAS KEPALA DI KOTA KENDARI, SULAWESI TENGGARA - -, SUHARNO (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006)
Since 2000, the agribusiness of super rice in Kendari city has progress. Several store and supermarket sell the super rice. There are many kind of super rice supplied from rice milling firm of near Kendari city especially from Konawe district, the aromatic super rice and non aromatic super rice. Related the condition, implemented the research, objectives is to know the factors which influences to super rice demand in Kendari city. The research implemented on several store which sell the super rice in Kendari city on December 2003. Researh method on the reasearh is survey to gather primary data on super rice marketing and collecting relevance data on government institutions. The research result indicated that the demand of aromatic super rice influenced by variabel : population income, and other rice price. Population income significantly influence of demand, it is showed 3,57. The other rice price significantly influenced to aromatic super rice rice demand it is showed 9,23. The total population significantly influenced to non aromatic super rice demand it is showed 2,14. The other rice influenced to non aromatic super rice demand it is showed 3,61. The result of research suggested to super rice producent that consument more like to choose the package with volume 5 kg than bigger package.
Keywords: Super Rice, Demand, Kendari City.